2023
DOI: 10.3389/fneur.2022.1054333
|View full text |Cite
|
Sign up to set email alerts
|

Variability in oxidative stress-related genes (SOD2, CAT, GPX1, GSTP1, NOS3, NFE2L2, and UCP2) and susceptibility to migraine clinical phenotypes and features

Abstract: IntroductionMigraine is a complex disorder with genetic and environmental inputs. Cumulative evidence implicates oxidative stress (OS) in migraine pathophysiology while genetic variability may influence an individuals' oxidative/antioxidant capacity. Aim of the current study was to investigate the impact of eight common OS-related genetic variants [rs4880 (SOD2), rs1001179 (CAT), rs1050450 (GPX1), rs1695 (GSTP1), rs1138272 (GSTP1), rs1799983 (NOS3), rs6721961 (NFE2L2), rs660339 (UCP2)] in migraine susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Papasavva et al investigated how variabilities in SNPs, including rs4880, rs1001179, and rs1050450, are related to susceptibility to the clinical phenotypes and features of migraine. What they found is that homozygosity for the minor T allele (rs1001179) was associated with the later age at the onset when compared to homozygosity for the more common allele C [ 45 ]. It would be interesting to further investigate the connection between TMD and migraine onset and depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Papasavva et al investigated how variabilities in SNPs, including rs4880, rs1001179, and rs1050450, are related to susceptibility to the clinical phenotypes and features of migraine. What they found is that homozygosity for the minor T allele (rs1001179) was associated with the later age at the onset when compared to homozygosity for the more common allele C [ 45 ]. It would be interesting to further investigate the connection between TMD and migraine onset and depression.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to further investigate the connection between TMD and migraine onset and depression. Considering SOD2 , no significant association was found for rs4880 variants for clinical features of migraine [ 45 ]. One case–control study reported that there was a lack of association between the SNPs of oxidative-stress-related genes (among which was rs4880 of SOD2 ) and chronic migraine [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the pathophysiology of the disease has not been fully elucidated, among the proposed mechanisms being implicated are the activation of the trigeminovascular system, cortical spreading depression, inflammation and vascular dysfunction [ 3 ]. Besides environmental factors, migraine is largely affected by genetic factors, with several genetic variants, each having a minor effect contributing to its liability [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%